2012
DOI: 10.1074/jbc.m111.260695
|View full text |Cite
|
Sign up to set email alerts
|

Role of Novel Rat-specific Fc Receptor in Macrophage Activation Associated with Crescentic Glomerulonephritis

Abstract: Background: Fc receptor-mediated macrophage activation is a major cause of glomerular damage in crescentic glomerulonephritis.Results: We investigated the role of a novel rat Fc receptor, Fcgr3-rs, in human and rat macrophage activation.Conclusion: We showed that this receptor prevents the cell signaling of its paralogue (Fcgr3).Significance: These results provide a novel way to inhibit Fc receptor-mediated cell activation in macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Fc receptor variation in other rat strains involving the presence or absence genomic sequence encoding a decoy Fc gamma receptor illustrates how genetic variation can modulate immunoreceptor signaling to affect renal disease risk 38 . These observations prompted our investigation to uncover further genetic variation in this pathway as a mechanism influencing renal injury in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Fc receptor variation in other rat strains involving the presence or absence genomic sequence encoding a decoy Fc gamma receptor illustrates how genetic variation can modulate immunoreceptor signaling to affect renal disease risk 38 . These observations prompted our investigation to uncover further genetic variation in this pathway as a mechanism influencing renal injury in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Here, to illustrate the practical utility of ABBA for differential methylation analysis in disease, we generated WGBS data in an established experimental rat model of crescentic glomerulonephritis (CRGN) (Aitman et al 2006). In this model, we and others have previously shown that susceptibility to CRGN is mediated by macrophages (Behmoaras et al 2008; Page et al 2012); therefore, we assayed CpG methylation at single-nucleotide resolution by WGBS in primary macrophages derived from Wistar Kyoto (WKY) and Lewis (LEW) isogenic rats (two strains discordant for their predisposition to develop CRGN). We used ABBA to carry out genome-wide differential DNA methylation analysis in primary bone-marrow derived macrophages (BMDM) derived from the disease-prone rat strain (WKY, r  = 4) and control strain (LEW, r  = 4)—see Materials and Methods for additional details on WGBS data generation and processing.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 1004 DMRs identified by ABBA, 427 overlapped with annotated genes (Table S3), and there was a significant enrichment for DMRs occurring within 1 kb of the gene boundaries ( P -value < 0.001), within exons ( P -value < 0.05), and within introns ( P -value < 0.05; Figure 3B). The genes that are within 1 kb of a DMR were enriched for pathways relevant to the pathophysiology of CRGN, including MAPK signaling (Ryan et al 2011), Phosphatidylinositol signaling (Wu et al 2014) and Fc gamma R-mediated phagocytosis (Page et al 2012) (Figure 3C). For comparison, the 207 DMRs identified by DSS overlapped with 45 genes (Table S4), which were enriched only for RNA degradation and metabolic pathways.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the absence of an Fc-related sequence ( Fcgr3-rs ) causes macrophage overactivity and NTN susceptibility in the WKY strain, whereas, conversely, the LEW strain, which has Fcgr3-rs , is resistant to NTN and shows no macrophage overactivity (Aitman et al, 2006; Page et al, 2012). Consistent with this, Fc-mediated bead phagocytosis levels were higher in WKY BMDMs than in LEW BMDMs.…”
Section: Discussionmentioning
confidence: 99%